The Effect of Strategic Alliance Knowledge Complementarity on New Product Innovativeness in China - Fang, Eric (Er) (Organization Science, 2011)
In emerging economies, firms use strategic alliances to access and learn from partners' knowledge and thus enhance their innovativeness, especially when the partners have complementary knowledge sets. However, differences in cultural and business practices, as well as a lack of trust between local and foreign firms, make it more difficult for both partners to absorb and integrate their complementary knowledge bases. In emerging economies, strategic alliances often are associated with weak legal and regulatory environments that make the integration of complementary knowledge sets challenging. Existing literature lacks a clear explanation of the effect of knowledge complementarity on new product innovativeness; in response, this article examines the moderating role of new product development process characteristics and external environmental factors. Among a sample of high-tech strategic alliances in China, new product development process interdependence and environmental dynamism positively moderate the effect of knowledge complementarity on new product innovativeness, whereas expropriation risks negatively moderate its effect.